(untitled) - Kitagawa, Joseph M. (Princeton, N.J., 1987)
Religious procession is a significant dimension of religion in South Asia. Processions are central not only in Hinduism, but also Islam, Christianity and Sikhism, which have large procession rituals. The last years have seen an increase in processions and ritualizations of space both in South Asia and in the South Asian Diaspora. Processions are religious display events and the increase in processions are functions of religious pluralism and competition about public space as well as economic prosperity and a revival of religious identities. Processions often bring together religion and politics since they are about public space, domination and contestation. Written by leading specialists on religious processions and ritualization of public space in South Asia and in the Diaspora, this volume presents current research on the interpretations of the role of processions, the recent increase in processions and changes in the procession traditions. "South Asian Religions on Display" will appeal to students and scholars of Asian studies, anthropology, religion and political science.